Value creation methods in a network approach. A case study of global engineering service providers - Niemczyk, Jerzy; Nowakowska-Cicio, Małgorzata (Metody kreowania wartości w podejściu sieciowym do strategii. Studium przypadku globalnego dostawcy usług inżynierskich, 2021)
The purpose of this study is to indicate the methods of identifying sources of value in a sample of four organizations which are global engineering service providers operating in the form of an interorganizational network. The empirical research used the network paradigm and the concept of organization description using network rents. The research was be based on an especially developed questionnaire survey using a structured survey questionnaire proposed by Trzaska. The study used a critical analysis of the relevant literature, desk research, and the author’s own analytical tools for measuring the value generated in interorganizational networks. The outcome of the study is the identification of the value creation methods applied by global engineering service providers and the indication of the possibility to measure them. The originality this research results from the new value creation methods applied by global engineering service providers
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 1 (59), s. 100-118
Keywords: strategic management; virtualization; organizational network; zarządzanie strategiczne; wirtualizacja; sieć organizacyjna